Parity and the association with diabetes in older women. - Fowler-Brown, Angela G; de Boer, Ian H; Catov, Janet M; Carnethon, Mercedes R; Kamineni, Aruna; Kuller, Lewis H; Siscovick, David S; Mukamal, Kenneth J (Diabetes Care, 2010)
OBJECTIVE: To examine the relationship of parity with diabetes and markers of glucose homeostasis in older women. RESEARCH DESIGN AND METHODS: We used data from the female participants in the Cardiovascular Health Study, a longitudinal cohort of adults aged >or=65 years. These data included an assessment of parity (baseline) and fasting serum levels of glucose, insulin, and medication use (baseline and follow-up). We estimated both the cross-sectional relationship of parity with baseline diabetes and the relationship of parity with incident diabetes. RESULTS: In unadjusted analyses, women with grand multiparity (>or=5 live births) had a higher prevalence of diabetes at baseline compared with those with fewer births and with nulliparous women (25 vs. 12 vs. 15%; P < 0.001). In regression models controlling for age and race, grand multiparity was associated with increased prevalence of diabetes (prevalence ratio 1.57 [95% CI 1.20-2.06]); with addition of demographic and clinical factors to the model, the association was attenuated (1.33 [1.00-1.77]). In final models that included body anthropometrics, the association was no longer significant (1.21 [0.86-1.49]). In those without diabetes at baseline, parity was not associated with incident diabetes or with fasting glucose; however, there was a modest association of parity with fasting insulin and homeostasis assessment model of insulin resistance. CONCLUSIONS: Grand multiparity is associated with diabetes in elderly women in cross-sectional analyses. This relationship seems to be confounded and/or mediated by variation in body weight and sociodemographic factors by parity status. In older nondiabetic women, higher parity does not pose an ongoing risk of developing diabetes.
Keywords: Aged; Body Weight; Cross-Sectional Studies; Diabetes Mellitus; Female; Humans; Parity; Pregnancy; Socioeconomic Factors